Study of dissolution profiles and desintegration of capsules containing the dried hydroethanolic extract of Calophyllum brasiliense - Carvalho,Helison de O. (2013)
Calophyllum brasiliense Cambess, Calophyllaceae, is of great interest in folk medicine and is used in the treatment of various diseases such as diabetes. Granules containing the hydroethanolic extract from the stem bark of C. brasiliense were obtained. The polyphenol content was standardized, and the average weight, disintegration, and the dissolution profiles of the capsules were determined after encapsulation. The capsules had an average weight of 574.5±8.0 mg. In vitro tests showed that the most efficient disintegration profile was in hydrochloric acid buffer (pH 1.2), with a capsule disintegration time within 9 min. The dissolution analysis showed a better uniformity of capsule content release when the test was performed in a hydrochloric acid buffer (pH 1.2), with a maximal release rate at 15 min (giving a polyphenol content of 4.38%, which corresponds to a concentration of 0.0080 mg/mL). In distilled water, the maximal release was reached at 20 min (giving a polyphenol content of 5.41%, which is equivalent to 0.0105 mg/mL). In phosphate buffer, the maximal release of capsule contents was reached at the end of the dissolution assay (30 min), with the lowest amount of released polyphenols (3.61%, which corresponds to a concentration of 0.0070 mg/mL). The encapsulated form of the hydroethanolic extract of C. brasiliense was shown to have the necessary traits of a desirable delivery agent, and the dissolution test was an effective analysis of this material's polyphenol release profile for the specific dosage form.